PENGARUH PEMBERIAN PUPUK KOMPOS TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT PINANG (Areca catechu L.) - Ida Nursanti; Yuza Defitri; Nanda Noviendra (Indonesian Journal of Thousand Literacies, 2023)
Palm empty fruit bunches compost is used to increase soil organic matter content, which is needed to improve soil physical properties and can increase soil fertility because this fertilizer contains nutrients, namely N (2.45%), K (0.82%) , Ca (0.84%), P(0.25%), Mg (0.45%), organic matter (62.70%), C/N ratio (14.90%), and pH 7.2 (Hayat and Andayani, 2014). This study aims to determine the effect of applying compost on the growth of areca nut (Areca catechu L.) seedlings. The materials used were Betara 2 months old areca nut seeds, TASPU brand of empty palm empty fruit bunch compost, and ultisol soil. The equipment used in this study were 5 kg polybags, hoes, machetes, knives, buckets, digital scales, cutter, oven, cloth meter, calipers, stationery and cameras. TKKS fertilizer treatment design (k) with five dose levels in 3 kg of planting medium, namely: k0 = control, k1 = 250 g, k2 = 500 g, k3 = 750 g, and k4 = 1000 g. Parameters observed were plant height, stem diameter, shoot dry weight, root dry weight, and soil analysis. Observational data were analyzed statistically using analysis of variance. If the results of the analysis of variance have a significant effect, continue using the DMRT test at the level of α = 5%. TKKS fertilizer treatment at a dose of 1000 g produced areca seedlings aged 2 months with a height of 48.55 cm, stem diameter of 13.84 mm, canopy dry weight of 34.31 g, root dry weight of 5269 g.